Nanoparticle Delivery of RIG-I Agonist Enables Effective and Safe Adjuvant Therapy in Pancreatic Cancer - Das, Manisit (Mol Ther, 2019)
Local immunomodulation can be a promising strategy to augment the efficacy and decrease off-target toxicities associated with cancer treatment. Pancreatic cancer is resistant to immunotherapies due to the immunosuppressive tumor microenvironment. Herein, we investigated a therapeutic approach involving delivery of a short interfering double-stranded RNA (dsRNA), specific to Bcl2, with 5′ triphosphate ends, by lipid calcium phosphate nanoparticles, in an orthotopic allograft KPC model of pancreatic cancer. Retinoic acid-inducible gene I (RIG-I)-like receptors can bind to 5′ triphosphate dsRNA (ppp dsRNA), a pathogen-associated molecular pattern, producing type I interferon, while Bcl2 silencing can drive apoptosis of cancer cells. Our approach demonstrated a robust enrichment of tumor tissue with therapeutic nanoparticles and enabled a significant tumor growth inhibition, prolonging median overall survival. Nanoparticles encapsulating dual-therapeutic ppp dsRNA allowed strong induction in levels of pro-inflammatory Th1 cytokines, further increasing proportions of CD8(+) T cells over regulatory T cells, M1 over M2 macrophages, and decreased levels of immunosuppressive B regulatory and plasma cells in the tumor microenvironment. Thus, these results provide a new immunotherapy approach for pancreatic cancer.